Does fiscal decentralisation foster regional investment in productive infrastructure? - Andreas Kappeler; Albert Solé-Ollé; Andreas Stephan; Timo Välilä (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The aim of this paper is to analyze the effect of revenue decentralization on the provision of infrastructure at the sub-national level. We estimate the effects of revenue decentralization and earmarked grant financing on the level of sub-national infrastructure investment in 20 European countries over the period 1990-2009. The results are interpreted in light of the predictions of the theory on fiscal federalism. We find that it is sub-national infrastructure investment that increases after revenue decentralization and not investment in redistribution. However, the effect of revenue decentralization is lower the higher the use of earmarked grants to fund infrastructure investment.
Keywords: H54; H77; H76; C23; 330; regional investment; fiscal federalism; dynamic panel data